2003
DOI: 10.1097/00126334-200303010-00015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of HIV-1 in Venezuela: High Prevalence of HIV-1 Subtype B and Identification of a B/F Recombinant Infection

Abstract: The authors assessed HIV-1 variability in two distinct areas of Venezuela (the capital Caracas and Margarita Island) through the analysis of blood specimens and clinical and epidemiologic data of 72 persons. Proviral DNA was evaluated through heteroduplex mobility assay (HMA) based on the envelope region. Additionally, FOK I restriction enzyme digestion assay was performed in all subtype B ED31/33 amplified products to check the presence of the typical Brazilian subtype B GWGR variant. Sequencing and phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
(48 reference statements)
1
20
0
Order By: Relevance
“…The city of Belem has one of the largest ports in the Brazilian Amazon and receives a great input of tourists throughout the year, while the city of Macapa is located next to several Indian tribes and borders countries such as Guyana, which generates a large population movement between two locations. The city of Belem shows the highest diversity of subtypes of HIV-1 in Brazil, having been identified the subtypes B, F, D, C and recombinant CRF02_AG subtype reflecting in this way, the same epidemiological profile found in almost all regions of Brazil (Sabino et al, 1996;Morgado et al, 1998;Ramos et al, 1999Vicente et al, 2000) and from South America (Marquina et al, 1996;Navas et al, 1999;Avila et al, 2002;Castro et al, 2003). The population group studied presented epidemiological characteristics which indicated that the heterosexual transmission of HIV-1 associated with sexual promiscuity, was the main way of virus dissemination.…”
Section: Hiv-1 Infection In the Brazilian Amazon Regionmentioning
confidence: 59%
“…The city of Belem has one of the largest ports in the Brazilian Amazon and receives a great input of tourists throughout the year, while the city of Macapa is located next to several Indian tribes and borders countries such as Guyana, which generates a large population movement between two locations. The city of Belem shows the highest diversity of subtypes of HIV-1 in Brazil, having been identified the subtypes B, F, D, C and recombinant CRF02_AG subtype reflecting in this way, the same epidemiological profile found in almost all regions of Brazil (Sabino et al, 1996;Morgado et al, 1998;Ramos et al, 1999Vicente et al, 2000) and from South America (Marquina et al, 1996;Navas et al, 1999;Avila et al, 2002;Castro et al, 2003). The population group studied presented epidemiological characteristics which indicated that the heterosexual transmission of HIV-1 associated with sexual promiscuity, was the main way of virus dissemination.…”
Section: Hiv-1 Infection In the Brazilian Amazon Regionmentioning
confidence: 59%
“…71,105 The subtypes A, E, G, H, J and K have been described to be prevalent in Burkina Faso, Mali, Nigeria, Ivory Coast, Gabon, and Democratic Republic of Congo, from where they have spread to South Europe, and Asia. 6,16,55,89,106,122 In South America, HIV-1 subtype B has been predominant in Brazil, followed by subtypes F, and C, with small proportion of subtype D. 13,15,28,30,39,94,114,116,127 In Argentina, Bolivia, Peru, Paraguay, Uruguay and Venezuela 21 and also in Caribbean Islands 140 these same subtypes have been found since the mid-1990s.…”
Section: Genomic Variabilitymentioning
confidence: 96%
“…13 Another subtype B with V3 loop motif GPGRTW was recently described in Venezuela. 21 Brazilian subtype C (or C Br ) has as a characteristic tetramer GPGQ, 13 also found in Portugal, 36 Japan, 99 and India. 80 In relation to the subtype F, Brazilian F Br possesses GPGR motif 13 that has a small difference compared to the Romanian subtype F R with predominant GPGQ motif, occasionally also observed in Brazil.…”
Section: Intra-subtypesmentioning
confidence: 98%
See 1 more Smart Citation
“…26,32 These groups have shown an ability to establish partnerships with research teams in the Northeast 36 and in other Latin American countries. 23,90 Furthermore, teams with independent production relating to coinfection between HIV and human T-lymphotropic virus (HIV/ HTLV) have emerged outside of the science and technology axis in the Southeast, like in Pará. 45 The monitoring on the progressive dissemination of HIV-1 subtype C in the Southern region of the country is impressive and comparable with the most refined molecular epidemiological studies worldwide.…”
Section: Anti-hiv/aids Vaccines and Molecular Epidemiology Of Hivmentioning
confidence: 99%